Analysis of Factors Causing Delays in Execution of Abc Apartement In Bekasi to Improve Time Performance - Yopi Lutfiansyah; Isma Shofa Mufida (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
The booming population growth is the reason it is difficult to have a comfortable place to live like housing in several big cities. Various apartment development projects in big cities are carried out by developers to fulfill public needs, besides the high land price and limited land, it is also the reason for the construction of apartments with adequate facilities. Bekasi City is one of the big cities that looks promising for vertical housing seekers because of the low price offered. The purpose of this research is to identify the factor causes of construction delays, the most dominant factors that causes the delay and find control measures consist of preventive and corrective action in order to minimize project delays. This research used quantitative research methods by distributing questionnaires to respondents who are project employees. This research used 3 stage questionnaire and the results will be conducted to test validity and reliability using statistical software and analysis of Importance Index (II). The results of this research the ABC apartment development project has 5 factors that most dominant, consisting of Late Payments by Owner (51.80%), Late Payments to Workers (51.17%), The Owner is Late for Making Decisions (49%), Unoptimal Worker Productivity (42.87%), and Lack of Manpower (42, 00%).